1986
DOI: 10.1161/01.atv.6.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Local variation in arterial wall permeability to low density lipoprotein in normal rabbit aorta.

Abstract: Normal rabbits were injected Intravenously with horseradish peroxldase (HRP) and 125 l-labeled human low density lipoprotein (LDL), and the aortas were pertuslon-flxed. Subsequent visualization of HRP In the aortas was produced by reaction of the tissue with diaminobenzldine and hydrogen peroxide. The lumlnal surface of the aortas showed many small punctate foci of brown reaction product to the HRP, which represented penetration of the HRP into the vessel wall. The foci were scattered over the luminal surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Ross mentioned that endothelial injury could result in release of growth factors, which could provide a mitogenic stimulus to smooth muscle cells. Stemerman et al 41 pointed out that gross endothelial damage is not necessary to mediate a large local increase in the uptake of low density lipoprotein (LDL). The term, endothelial injury, has also been used to indicate endothelial cell dysfunction.…”
Section: Intramural Stress Hypothesis For Atherogeneslsmentioning
confidence: 99%
“…Ross mentioned that endothelial injury could result in release of growth factors, which could provide a mitogenic stimulus to smooth muscle cells. Stemerman et al 41 pointed out that gross endothelial damage is not necessary to mediate a large local increase in the uptake of low density lipoprotein (LDL). The term, endothelial injury, has also been used to indicate endothelial cell dysfunction.…”
Section: Intramural Stress Hypothesis For Atherogeneslsmentioning
confidence: 99%
“…One of the first issues that one must address to develop an understanding of the mass transport in these vessels is whether such transport is driven by diffusion and/or convection. In previous mass transport studies of the aorta, rats were injected with a macromolecular tracer, such as horseradish peroxidase (HRP), and were killed after different circulation times (11,35). In an examination of the animals' aortas en face, HRP was found to traverse the endothelium in rare localized spots, rather than uniformly.…”
mentioning
confidence: 99%
“…Previous investigation with horseradish peroxidase (HRP) has revealed brown spots with an LDL concentration 47 times greater than the noncolored regions after a short circulation time, but the nature of those leaky spots has not been elucidated. 5 More recently, it has been shown that almost all mitotic cells in aortic endothelium are leaky to EBA, 6 but the data were not analyzed in terms of their regional distribution, the process of lateral diffusion, or hemodynamic influences. To address the questions of: 1) the initial sites of macromolecular entry, 2) the process of lateral diffusion in the media of vessel wall, and 3) the hemodynamic influences on atherogenesis, we used EBA and HRP as tracers to study the macromolecular transport across arterial and venous endothelia in normal rats.…”
mentioning
confidence: 99%